An innovative high-throughput genome releaser for rapid and efficient PCR screening - Yuan, Guoliang; Salalila, Aljon; Hwang, Sungjoo; Deng, Zhiqun Daniel; Deng, Shuang (Frontiers in Bioengineering and Biotechnology, 2025)
High-throughput PCR screening is vital in synthetic biology and metabolic engineering, enabling rapid and precise analysis of genetic modifications. However, current methods face challenges including inefficient DNA extraction, high variability across sample types, scalability limitations, and the high cost of template DNA extraction. To address these common challenges, we developed a High-Throughput Genome Releaser (HTGR). This innovative device utilizes a squash-based method for rapid, cost-effective, and efficient DNA extraction, optimized for subsequent PCR reactions. After testing various synthetic materials, we selected a plastic that closely mimics the smooth surface and compression properties of microscope slides, ensuring reliable and consistent performance. The device comprises a 96-well plate and a Shear Applicator, designed for both manual and automated operation, and is compatible with standard liquid-handling robotic platforms. This compatibility simplifies integration into high-throughput PCR workflows. Additionally, we developed software to support its automated functions. Our results demonstrated that the specially engineered 96-well plate and HTGR effectively squash fungal spores, releasing sufficient genomic DNA for PCR screening with 100% efficiency. The genome releaser enables the preparation of PCR-ready genomic DNA from 96 samples within minutes, eliminating the need for an extraction buffer. Its adaptability to a wide range of microorganisms and cell types makes it a versatile tool that could significantly advance biomanufacturing processes.